English To Punjabi Script Converter System For Proper Nouns Using Hybrid Approach (International Journal of Scientific Research and Management (IJSRM), 2015)
The most commonly faced problem with translators is to translating proper nouns like names and technical terms. In this research work we have proposed a English to Punjabi transliteration system for proper nouns that involves person names including male and female from Indian and foreign origin, continent names, city names, country names, state names etc. A hybrid approach is used to transliterate the proper nouns written in English text into its equivalent Punjabi text. Hybrid approach used in the proposed system is a combination of three approaches which are direct approach which is also known as dictionary lookup approach, rule based approach and statistical machine translation approach. The accuracy of the overall system highly depends upon the data provided for the training phase and data available in the parallel corpus. Various test cases have been performed on the proposed system and accuracy of proposed system is 90.4%. In future, this accuracy can be further improved by increasing the corpus size and using some more rules.